PREVALENCE OF METABOLIC ASSOCIATED FATTY LIVER DISEASE WITH CONTROLLED ATTENUATION PARAMETER AND LIVER STIFFNESS MEASUREMENTS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Sekarsari, Yulia; Pramono, R. Bowo; Susanti, Vina Yanti; Ikhsan, M. Robikhul; Sinorita, Hemi; Ratnasari, Neneng; Purba, Helmi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Type 2 diabetes mellitus (T2DM) increases the risk of metabolic-associated fatty liver disease (MAFLD). We aimed to investigate the proportion of patients with T2DM and MAFLD and the factors associated with MAFLD among patients with T2DM in Dr. Sardjito Hospital, Yogyakarta, Indonesia. METHODOLOGY In a cross-sectional design study, 50 patients with T2DM were enrolled. Liver steatosis and fibrosis were assessed by Fibroscan. RESULTS The prevalence of MAFLD was 64%. Patients with steatosis and fibrosis had higher triglyceride levels than those with steatosis without fibrosis. The proportion of significant fibrosis (F2) and advanced fibrosis (F3) and cirrhosis (F4) were 20%,16%, and 4%, respectively. By multivariable analysis, triglyceride (OR:2,001; 95% CI: 1,570-2,054; p = 0,041) and presence of diabetes complication (OR:2,046; 95% CI: 1,865-3,728; p = 0.033) were associated with MAFLD. CONCLUSION Patients with T2DM have a high proportion of MAFLD and its presence is associated with serum triglyceride levels and the presence of diabetes complications.